EFEKTIVITAS PEMBUATAN PERATURAN DAERAH KHUSUS DI PROVINSI PAPUA: STUDI MAJELIS RAKYAT PAPUA - Hamjah Bonso; Herman Lawelai (Jurnal Studi Ilmu Pemerintahan, 2020)
Abstract: The presence of the special autonomy law in Papua has had an impact on institutions. This can be seen with the formation of the Papua People's Assembly (MRP). This study aims to determine the effectiveness of making specific regional regulations in the province of Papua. This study uses a "triangulation" method that combines qualitative and quantitative methods with data collection techniques, namely interviews, documentation, and questionnaires. The results showed that the Papuan People's Assembly (MRP) in making special regional regulations (Perdasus) was already quite effective, which can be seen from the involvement of the MRP which scored 1,35 (moderate), MRP commitment 2,05 (high), the role of MRP 2,0 (high), and the implementation of the MRP mechanism 2,1 (high).